Sangria aberta ou artéria do progresso: a emigração ibérica oitocentista nos debates sobre a colonização do além-mar - Goncalves, Paulo Cesar [UNESP] (My University, 2013)
Using documents produced by the Geographical Society of Lisbon and the Geographical Society of Madrid, and studies of some of theirs most important members, this article focuses on the importance of emigration in the nineteenth century Iberian debates within the two entities on issues as empire, colonization and economic development of both countries.

Utilizando documentos produzidos pela Sociedade de Geografia de Lisboa e pela Sociedade Geográfica de Madri, além de estudos de alguns de seus mais importantes membros, este artigo enfoca a importância da emigração ibérica oitocentista nos debates ocorridos no âmbito das duas entidades em relação a temas como império, colonização e desenvolvimento econômico dos dois países.
Keywords: Portugal; Spain; Colonization; Emigration; Geography; Portugal; Espanha; Colonização; Emigração; Geografia